FLUID INCLUSIONS CHARACTERISTICS AND ORE-FORMING EVOLUTION OF JINWOZI GOLD DEPOSIT - Pan X.F.; Liu W. (My University, 2006)
Jinvozi Gold Deposit lies in the mid ore-forming band of Beishan Belt, Gansu Province. The analytical result of Raman spectrometric measurement for fluid inclusions in quartz shows that HO2-NaCl, H2O-CO2-CH4, -NaCl, or H2 O-CO2 -NaCl systems are present during ore-forming processes. In Pyrite-Quartz (P-Q) stage, the Characteristics of aqueous fluid inclusions are the same as those of carbonaceous fluid inclusions in NO.3 auriferous quartz vein. Thus, the geological hydrothermal solution showing mono-phase is unfit for deposition of gold and other heavy metals. When Quartz-Pyrite and Multi-Metal-Sulfide (Q-P & MMS) stage, homogeneous fluid fractionized into two immiscible fluid with different components and total homogenization temperature that one is low-salinity, lowtemperature, aqueous fluid, and the other is high-salinity, high-temperature, CO2 -rich (and a little of CH4,) fluid. A big difference about 100°C in total homogenization temperature and high salinity in CO2-rich fluid are evidence of no fluid mixing process during large-scale ore deposition stages. During P-Q stage, and Q-P & MMS stage in NO. 210 network auriferous quartz vein, two different hydrothermal solution, aqueous solution and low salinity and CO2 -rich (and a little of CH4,) fluid exist in ail ore-forming stages. Thus, NO.210 vein shows no direct relevance with immiscible mechanism. In No.210 meshwork gold deposit controlled by pyritization mylonite, mylonitization and pyritization breccias, its homogeneous temperature and salinity of ore-forming fluid in initial stages (P-Q) are similar to those present in later leading ore-forming stages (Q-P & MMS), because quartz-vein formed in initial stages are altered by replacement and dissemination.
Keywords: FLUID INCLUSIONS; IMMISCIBILITY; JINWOZI GOLD DEPOSIT